Amitriptyline and nortriptyline induce ocular toxicity in early life stage zebrafish (Danio rerio) - Jafari, Marwin; Magnuson, Jason T.; Essfeld, Fabian; Eilebrecht, Sebastian; Brotzmann, Katharina; Pampanin, Daniela M. (Comparative biochemistry and physiology. Part C, Toxicology & pharmacology, 2025)
The global use of antidepressants has steadily increased, raising concern to aquatic ecosystems due to the incomplete removal during wastewater treatment. Tricyclic antidepressants (TCAs) act on the neuronal system by inhibiting the reuptake of serotonin and norepinephrine. However, despite visual function being heavily dependent on the neuronal system, a knowledge gap remains regarding the ocular toxicity of TCAs. To bridge this knowledge gap, zebrafish (Danio rerio) embryos were exposed to sublethal test concentrations of amitriptyline (AMI, 0.3 to 300 μg/L nominal, 2.04 to 234 μg/L measured) and nortriptyline (NOR, 0.03 to 300 μg/L nominal, >0.107 to 20.7 μg/L measured), with the lowest test concentrations being environmentally relevant. Visual function was assessed with the optokinetic response assay, eye structure development was assessed histologically, and gene expression changes were analysed via transcriptomic profiling. Larval zebrafish (120 h post fertilization (hpf)) exposed to 4.99 and 234 μg/L of AMI exhibited a 26 % and 86 % decrease in the number of eye saccades respectively, with zebrafish exposed to 20.7 μg/L of NOR exhibiting a 65 % decrease. Histological analysis indicated a significant increase of the retinal pigment epithelium thickness after exposure to 234 μg/L of AMI and 20.7 μg/L of NOR. Transcriptomic analysis resulted in 1207 and 2742 differentially expressed genes across both AMI and NOR treatment groups respectively, including genes involved in vision, synaptic signaling, and neuronal development. These findings demonstrate that sublethal concentrations of AMI and NOR affect early life stage zebrafish visual development, which may be sensitive endpoint that could be incorporated into ecological risk assessments.
Gesehen am 12.02.2026